Wildlife Conservation and Management: Challenges and Strategies - Gupta, Swapnil; Kumaresan , P. R.; Saxena , Ankur; Mishra, Manish Raj; Upadhyay , Lalit; Arul Sabareeswaran T. A.; Alimudeen S.; Magrey, Ashiq Hussain (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
This article delves into the critical issues and strategies related to wildlife conservation and management in the context of the contemporary environmental crisis. It highlights the major challenges that wildlife faces, including habitat destruction and fragmentation, climate change impacts, the threat of illegal wildlife trade and poaching, the introduction and spread of invasive species, and the detrimental effects of pollution. The article emphasizes the importance of effective strategies to counter these challenges, such as habitat conservation and restoration, climate change mitigation, combating illegal wildlife trade, managing invasive species, and pollution control. It argues for a multifaceted and collaborative approach, involving governments, NGOs, local communities, and individuals, to ensure the preservation of wildlife and natural ecosystems. The overarching goal is to strike a balance between human development and wildlife conservation, thereby securing a sustainable future for our planet's biodiversity.